Physical oceanographic profiles of seven CTD casts from Gulf of Ancud into Comau Fjord in 2016 - Marlene Wall; Kristina K Beck; Nur Garcia-Herrera; Gertraud M Schmidt-Grieb; Jürgen Laudien; Juan Höfer; Günter Försterra; Christoph Held; Gernot Nehrke; Juan Pablo Espinoza; Matthias Woll; Martin Graeve; et al. (PANGAEA, 2023)
In September 2016, CTD measurements were carried out along the Comau Fjord, Chile, from the head of the fjord to the mouth of the fjord. CTD measurements were taken at a total of 6 stations from the surface to the bottom of the fjord and temperature, salinity, fluorescence, density, oxygen and pH per meter of water depth were recorded.